EFEKTIVITAS PENGGUNAAN EKSTRAK TAUGETERHADAP VIABILITAS LAMA PERENDAMAN BENIHTOMAT CERI (Lycopersicumesculentum) VARIETAS LOKAL - Khadijah, Khadijah; Saputra, Whin Themas Mico; Yunita, Dinda (Universitas Gajah Putih, 2024)
This research was carried out at the Laboratory of the Faculty of Agriculture, Gajah Putih University, Takengon, which was carried out from 1 August 2024 to 10 August 2024. The aim of this research was to find out how much influence concentration and soaking time had on the viability of local cherry tomato seeds. The results of this research were that the concentration of bean sprout extract had a significant effect on growth potential at 5 and 10 days after sowing, wet stover weight at 5 days after sowing. The germination capacity at the age of 5 and 10 days after sowing has a very significant effect and the weight of the wet stover at the age of 10 days after sowing. The length of soaking time for bean sprout extract did not significantly affect the viability of cherry tomato seeds but tended to produce the highest growth potential, germination capacity and growth speed.